Perancangan Aplikasi Presensi berbasis QR Code untuk Efisiensi Manajemen Kehadiran Siswa MAN 1 Bima - Fitriati, Ita; fitrianingsih, nur; Ilyas, Ilyas; Wahyudin, Wahyudin (Inverted: Journal of Information Technology Education, 2023)
Currently the presence system must begin to be implemented in schools that uphold school administration management improvements in order to produce superior schools. One of the schools that upholds these improvements is MAN 1 Bima located in Bima Regency, West Nusa Tenggara, which is also a research location and implementation of the developed product. The objectives of the research include: 1) Designing a QR code-based student attendance application and knowing the feasibility level of the application. 2) Measuring the efficiency of the successful implementation of the attendance application in improving student attendance management at MAN 1 Bima. This research uses the RD method. The stages in this study include four stages, namely (1) planning, (2) design, (3) coding, (4) testing. The product has gone through the Validation stage to determine the feasibility of the designed application, which was carried out on 2 media expert validators with a Validation value of 84% (very feasible category), while product implementation was carried out on teachers and students at MAN 1 Bima, with an average result of 90%. The efficiency of student attendance management includes 9 items of assessment instruments as much as 87% Saat ini sistem presensi  harus mulai diterapkan pada sekolah sekolah yang menjunjung tinggi perbaikan manajement administrasi sekolah dalam rangka menghasilkan sekolah yang unggul, Salah satu sekolah yang menjunjung perbaikan tersebut adalah MAN 1 Bima yang berada di Kabupaten Bima Nusa Tenggara Barat, yang sekaligus menjadi lokasi penelitian dan implementasi dari produk yang dikembangkan. Tujuan dari penelitian diantaranya: 1) Merancang aplikasi absensi siswa berbasis QR code dan mengetahui tingkat kelayakan aplikasi. 2) Mengukur Efisiensi keberhasilan implementasi aplikasi abensi pada perbaikan manajemen kehadiran siswa MAN 1 Bima. Penelitian ini menggunakan Metode RD. Tahapan dalam penelitian ini meliputi empat tahapan, yaitu (1) planning (perencanaan), (2) desain, (3) coding (pengkodean), (4) Pengujian. Produk telah melalui tahap Validasi untuk mengetahui kelayakan aplikasi yang dirancang, yang dilakukan terhadap 2 validator ahli media dengan nilai Validasi sebesar 84% (kategori sangat layak), sedangkan implementasi produk dilakukan terhadap guru maupun siswa di MAN 1 Bima, dengan hasil rerata 90%. Adapun Efisiensi manajemen kehadiran siswa meliputi 9 item instrument penilaian sebanyak 87 %.